(untitled) - Võ, Minh Lâm (Can Tho, 2008)
This study investigated impact of authentic materials on learner's speaking ability in term of teaching English to non-English major students at the foreign language center of Dong Thap community college.
Keywords: English language,Tiếng Anh,English language,Tiếng Anh; Study and teaching,Dạy và học,Research,Nghiên cứu